MITOCHONDRIAL THERAPIES IN AGING AND AGE-RELATED DISEASES - Olga Borysova (Anti-Aging Eastern Europe, 2025)
Mitochondria, essential for cellular energy production and metabolic homeostasis, undergo progressive dysfunction with aging, contributing to a range of age-related diseases. Key mechanisms underlying mitochondrial deterioration include impaired mitophagy, cardiolipin remodeling, genetic instability, and excessive reactive oxygen species (ROS) accumulation. These dysfunctions are critical in the aging process, affecting brain function, cardiovascular health, metabolic health, fertility, and stem cell maintenance. This article explores the molecular basis of mitochondrial aging and its impact on age-related diseases, highlighting emerging therapeutic strategies from small molecules to mitochondrial transfer techniques that could transform aging research. As mitochondrial-targeted therapies evolve, they offer new hope for mitigating aging-associated decline and improving overall healthspan.